PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 13 GAJAH SAKTI KECAMATAN MANDAU - Windarti, Arie; Lazim N, Lazim N; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was conducted because of the low class IV student learning outcomes in social studies with an average of 68.20, and below the minimum completeness criteria (KKM) set by the school at 70 in the second semester of the 2015/2016 academic year. Meanwhile, the number of students who reached KKM only 11 students (44.00%) while those not reached KKM amounted to 14 people (56.00%). The purpose of this research to improve learning outcomes IPS fourth grade students of SD Negeri 13 Gajah Sakti subdistrict Saber with the application of learning models make a match. The results of observation of activities of teachers in the first cycle of activity first meeting is 45.80% less category, at a second meeting be 58.30% enough category. At the first meeting of the second cycle increased to 79.25% both categories, and the second meeting increased again 95.80%. While the observation of the activities of student activity can be seen from the first cycle of the first meeting is 41.67% less category, at a second meeting be 54.17%. At the first meeting of the second cycle of 75.00% and second dipertemuan increased to 91.70%. IPS learning outcomes from initial data to the UH 1 which is an average of 68.2 increased to an average of 69.4 with an increase of 1.76% to 2 UH increased to an average of 81.4 with an increase of 19.35%.Key Words: Make A Match, learning outcomes IPS